(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The democratic and human-rights based on intent ofInclusive Education is defined in the Salamanca Statement, and represented inthe “recognition of the need to work towards ‘schools for all’ – institutionswhich include everybody, celebrate differences, support learning, and respondto individual needs’. Education for All (EFA), which represents an internationalcommitment to ensure that every child and adult receives basic education ofgood quality, is based both on a human rights perspective, and on the generallyheld belief that education is central to individual well-being and nationaldevelopment.